Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the equation [tex]\(-3(x-1)=x-5\)[/tex], we can follow these steps:
### Step-by-Step Solution:
1. Distribute the -3 on the left side:
[tex]\[ -3(x-1) = x - 5 \][/tex]
Apply the distributive property to the left side:
[tex]\[ -3x + 3 = x - 5 \][/tex]
2. Combine like terms:
Bring all terms involving [tex]\(x\)[/tex] to one side of the equation and constants to the other side. To do this, add [tex]\(3x\)[/tex] to both sides:
[tex]\[ -3x + 3 + 3x = x - 5 + 3x \][/tex]
Simplify:
[tex]\[ 3 = 4x - 5 \][/tex]
3. Isolate the [tex]\(x\)[/tex] term:
Add 5 to both sides to get the constant term on the right side:
[tex]\[ 3 + 5 = 4x - 5 + 5 \][/tex]
Simplify:
[tex]\[ 8 = 4x \][/tex]
4. Solve for [tex]\(x\)[/tex]:
Divide both sides by 4:
[tex]\[ \frac{8}{4} = \frac{4x}{4} \][/tex]
Simplify:
[tex]\[ x = 2 \][/tex]
### Verification:
To ensure no mistakes were made, substitute [tex]\(x = 2\)[/tex] back into the original equation [tex]\(y = -3(x-1)\)[/tex] and [tex]\(y = x-5\)[/tex]:
1. First equation [tex]\(y = -3(x - 1)\)[/tex]:
[tex]\[ y = -3(2 - 1) = -3(1) = -3 \][/tex]
2. Second equation [tex]\(y = x - 5\)[/tex]:
[tex]\[ y = 2 - 5 = -3 \][/tex]
Since both equations yield [tex]\(y = -3\)[/tex] when [tex]\(x = 2\)[/tex], the solution satisfies both equations. Therefore, there are no additional solutions.
### Conclusion:
The solution to the equation [tex]\(-3(x-1)=x-5\)[/tex] is:
[tex]\[ x = 2 \][/tex]
There are no other solutions. Thus, the final answer is:
[tex]\[ \boxed{2} \][/tex]
### Step-by-Step Solution:
1. Distribute the -3 on the left side:
[tex]\[ -3(x-1) = x - 5 \][/tex]
Apply the distributive property to the left side:
[tex]\[ -3x + 3 = x - 5 \][/tex]
2. Combine like terms:
Bring all terms involving [tex]\(x\)[/tex] to one side of the equation and constants to the other side. To do this, add [tex]\(3x\)[/tex] to both sides:
[tex]\[ -3x + 3 + 3x = x - 5 + 3x \][/tex]
Simplify:
[tex]\[ 3 = 4x - 5 \][/tex]
3. Isolate the [tex]\(x\)[/tex] term:
Add 5 to both sides to get the constant term on the right side:
[tex]\[ 3 + 5 = 4x - 5 + 5 \][/tex]
Simplify:
[tex]\[ 8 = 4x \][/tex]
4. Solve for [tex]\(x\)[/tex]:
Divide both sides by 4:
[tex]\[ \frac{8}{4} = \frac{4x}{4} \][/tex]
Simplify:
[tex]\[ x = 2 \][/tex]
### Verification:
To ensure no mistakes were made, substitute [tex]\(x = 2\)[/tex] back into the original equation [tex]\(y = -3(x-1)\)[/tex] and [tex]\(y = x-5\)[/tex]:
1. First equation [tex]\(y = -3(x - 1)\)[/tex]:
[tex]\[ y = -3(2 - 1) = -3(1) = -3 \][/tex]
2. Second equation [tex]\(y = x - 5\)[/tex]:
[tex]\[ y = 2 - 5 = -3 \][/tex]
Since both equations yield [tex]\(y = -3\)[/tex] when [tex]\(x = 2\)[/tex], the solution satisfies both equations. Therefore, there are no additional solutions.
### Conclusion:
The solution to the equation [tex]\(-3(x-1)=x-5\)[/tex] is:
[tex]\[ x = 2 \][/tex]
There are no other solutions. Thus, the final answer is:
[tex]\[ \boxed{2} \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.